2013
DOI: 10.1523/jneurosci.0492-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of Prospective Tasks in the Human Prefrontal Cortex under Varying Task Loads

Abstract: Successful realization of planned actions requires the brain to encode intentions over delays. Previous research has indicated that several regions in the rostral or anterior prefrontal cortex (PFC) encode delayed intentions. However, different processes may encode the same future task depending on task load during the delay. This difference may depend on the computational resources available when the delay is occupied with an ongoing task and when it is task-free. Here we directly investigated and compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 51 publications
6
51
0
1
Order By: Relevance
“…speaking a language different from the one used previously. This interpretation is consistent with other studies that have linked the precuneus to a fronto-parietal control network responsible for directing selective attention (Dosenbach et al, 2007;Utevsky, Smith, & Huettel, 2014), and to studies showing the involvement of the precuneus in selecting and maintaining the intention of performing specific future tasks (prospective intentions, Burgess, Gonen-Yaacovi, & Volle, 2011;Momennejad & Haynes, 2013;Schacter, Addis, & Buckner, 2007;Soon, He, Bode, & Haynes, 2013). During the language execution phase we find distinct neural activity depending on which language is spoken.…”
Section: Discussionsupporting
confidence: 92%
“…speaking a language different from the one used previously. This interpretation is consistent with other studies that have linked the precuneus to a fronto-parietal control network responsible for directing selective attention (Dosenbach et al, 2007;Utevsky, Smith, & Huettel, 2014), and to studies showing the involvement of the precuneus in selecting and maintaining the intention of performing specific future tasks (prospective intentions, Burgess, Gonen-Yaacovi, & Volle, 2011;Momennejad & Haynes, 2013;Schacter, Addis, & Buckner, 2007;Soon, He, Bode, & Haynes, 2013). During the language execution phase we find distinct neural activity depending on which language is spoken.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the observed exploration of alternative strategies does not seem to be driven by unreliability, conflict or errors, as in previous studies (Botvinick et al, 2001; Collins and Koechlin, 2012; Daw et al, 2006; Donoso et al, 2014; Nassar et al, 2010). Rather, our findings would better relate with previous evidence showing the involvement of MPFC in deciding which task to perform in the future (Haynes et al, 2007; Momennejad and Haynes, 2013; Soon et al, 2013; Wisniewski et al, 2014). Note, however, that in the above-mentioned studies a (mostly a priori specified) rule was decoded from brain activity, whereas our study decoded stimulus features.…”
Section: Discussionsupporting
confidence: 65%
“…Only voxels that showed enhanced signal in PM+OG trials were included. The reverse contrast (OG-only > PM+OG trials) revealed a network of voxels, including in the anterior medial prefrontal cortex, that deactivated with the addition of the PM task (Gilbert, 2011; Momennejad & Haynes, 2012, 2013). However, pattern classification of PM stimulus processing (target and distractor pictures) from these regions was at chance levels and therefore these voxels were excluded from further analysis.…”
Section: Methodsmentioning
confidence: 99%